Prevalence and correlates of psychological distress among cancer patients in a tertiary care hospital in northern India - Mason, Amita; Juyal, Ruchi; Das, Sai Chandan; Shikha, Deep; Saini, Sunil; Semwal, Jayanti (International Journal Of Community Medicine And Public Health, 2019)
Background: Patients diagnosed with cancer are usually exposed to high level of mental stress and hence invariably lend in psychological distress. This study aimed to estimate the prevalence of psychological distress amongst cancer patients and determine its association with socio-demographic factors. Methods: This hospital based cross-sectional study was conducted at a cancer research institute of district Dehradun. Purposive sampling was used to select the hospital and recruiting patients. All eligible patients, giving written consent for the study were interviewed and distress related information was gathered using the Hospital Anxiety and Depression Scale (HADS). The data were collected for two months and sample size of 208 was achieved. Data was entered in SPSS 22.0 and association of different variables with psychological distress was determined by chi-square test.. Results: The mean age of the surveyed cancer patients was 51.05±15.68 years and the male female ratio was 1.7. Prevalence of psychological distress was found to be 38.5% and significantly more female patients than male patients (47.4% and 33.3% respectively) had distress. The association between psychological distress and increasing age, sex, literacy and employment status was found to be significant. Conclusions: Approximately 39% of cancer patients had psychological distress (anxiety/ depression/ both). The prevalence of psychological distress was found to be significantly higher in female patients, older age, patients with no formal education, unemployment and lower socio-economic status. Appropriate psychiatric interventions/ counselling following diagnosis and during therapy may be effective in reducing distress and improving quality of life in cancer patients.